A New Wideband, Low Insertion Loss, High Linearity SiGe RF Switch - Cheon, Clifford D.; Cho, Moon-Kyu; Rao, Sunil G.; Cardoso, Adilson S.; Connor, Jeffrey D.; Cressler, John D. (IEEE microwave and wireless components letters, 2020)
This letter presents new wideband single-pole double-throw (SPDT) RF switches utilizing SiGe heterojunction bipolar transistors (HBTs) for both series and shunt switches. SiGe HBT, when used as a series switch, exhibits small parasitic components compared to bulk CMOS, which improves insertion loss at high frequency and supports wider bandwidth. For a series switch, three configurations are proposed: using the collector as an input (CI), using the emitter as an input (EI), and using a combination of the two in an antiparallel (AP) fashion. While all three configurations exhibit similar performance, the SPDT switch with the EI SiGe HBT exhibits the best insertion loss and isolation achieving dc-to-above 110-GHz bandwidth, 2.5 dB of insertion loss, and 27.3 dB of isolation at 60 GHz. The SPDT switch with AP SiGe HBT pair exhibits the highest linearity, with 15.6 dBm of input 1-dB compression point (IP 1 dB) at 10 GHz. With 0.61 mW of power dissipation, these new SPDT switches using SiGe HBTs exhibit similar performance to silicon-on-insulator (SOI) CMOS while obtaining higher power capability among conventional series-shunt SPDT designs.